Left atrial remodelling in competitive adolescent soccer players - Ascenzi, F.; Cameli, M.; Lisi, M.; Zacà, V.; Natali, B.; Malandrino, A.; Benincasa, S.; Catanese, S.; Causarano, A.; Mondillo, S. (International Journal of Sports Medicine, 2012)
Left atrial (LA) enlargement and improved myocardial diastolic properties are a component of athlete's heart. We performed a longitudinal study involving adolescent athletes to investigate the impact of training on LA remodelling and diastolic function. 21 competitive adolescent soccer players were enrolled and engaged in an 8-month training program. Echocardiographic analysis was performed at baseline, after 4 and 8 months. We assessed diastolic function by Doppler tissue imaging and we analyzed LA adaptations by 2D speckle-tracking echocardiography. After 4 months, LA mean volume index significantly increased (Delta=5.47±4.38 mL/m2, p</= 0.0001). After 8 months, a further increase occurred (Delta =8.95±4.47 mL/m2, p</= 0.0001). A higher E velocity (p=0.001; p=0.001), a greater E/A ratio (p=0.002; p=0.0009), a higher e' peak (p= 0.005; p=0.001), and a greater e'/a' ratio (p=0.01; p=0.0006) were observed at 4 and at 8 months, respectively. E/e' ratio significantly decreased after 8 months (p?0.005). Global peak atrial longitudinal strain and global peak atrial contraction strain values significantly decreased after 8 months (p=0.0004, p=0.01, respectively). An 8-month training program is associated with LA dimensional and functional training-specific adaptations in competitive adolescent soccer players. Myocardial diastolic properties can improve after training also in subjects already presenting with features of athlete's heart.